N-Doped graphene frameworks with superhigh surface area: excellent electrocatalytic performance for oxygen reduction. Issue 5 (14th January 2016) - Cui, H. J.; Yu, H. M.; Zheng, J. F.; Wang, Z. J.; Zhu, Y. Y.; Jia, S. P.; Jia, J.; Zhu, Z. P.
Abstract : N-Doped graphene frameworks with a large surface area and a graphitic-N-dominant C–N configuration are synthesized, which display excellent performance for the ORR. Abstract : N-Doped carbon materials are promising candidates as alternative catalysts to noble metals in promoting the oxygen reduction reaction (ORR) in fuel cells. However, methods to further reduce the ORR overpotential and improve related kinetics remain to be developed. This study reports that N-doped graphene frameworks (NGFs) synthesized from the rapid pyrolysis of solid glycine particles in the presence of sodium carbonate, display an extremely large specific surface area (1760 m 2 g −1 ) and a graphitic-N-dominant C–N configuration. The NGFs can efficiently catalyze the electrochemical reduction of molecular oxygen into water following a 4e pathway, with a low overpotential (0.98 V of onset potential vs . RHE), very high kinetic limiting current density (16.06 mA cm −2 ), and turnover frequency (121 s −1 ), much better than the commercial Pt/C catalyst.